A Simple Test for Measuring Platelet Aggregation - Holdrinet, A; Ewals, M; Haanen, C (Thrombosis and Haemostasis, 1969)
A simple method of measuring platelet aggregation is described which is suitable as a screening test in studies of haemostasis. This test is based on the phenomenon that blood platelets present in blood in the form of aggregates, are more rapidly deposited during centrifugation than platelets present in dispersed form.A comparative study was made of platelet concentration in the supernatant plasma of slowly centrifuged EDTA-blood, heparinized blood and heparinized blood mixed with ADP (end concentration 4.5 μg/ml).As expected, the platelet concentration was always highest in the EDTA-plasma because EDTA prevents platelet aggregation and disperses platelet aggregates if already present. The difference in platelet count between EDTA-plasma and heparin-ADP, expressed as per cents of the count in EDTA-plasma, was called ADP-aggregation. The ADP-aggregation exceeded 79% in 35 normal subjects. It was lower than 79% in 6 of 9 von Willebrand patients, 11 of 13 relatives of these patients and 7 of 8 uraemic patients.The percentual difference in platelet concentration between EDTA-plasma and heparinized plasma was called spontaneous aggregation. This was significantly lower in von Willebrand patients and their relatives than in the control group. By comparing all groups of patients collectively with the normal control group, an even more marked difference in spontaneous aggregation was found.